THE EFFECT OF CAPITAL COST ON COMPANY VALUE WITH GOOD CORPORATE GOVERNANCE AS A MODERATION VARIABLE - Judijanto, Loso; Mahdi, Mahdi; Wati, Indah; Zaman, M Nuruz; Zaki, Achmad (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract Company value is a very important aspect and is of concern to external parties such as investors, stakeholders, government officials, partners, and so on. As the value of the company increases, the company's image will become better amidst the elements that the researcher mentioned earlier. There are a number of factors that can influence company value, including Mode Costs which researchers can influence. In contrast to previous research, this research uses the Good Corporate Governance variable as a moderating variable which researchers believe can strengthen the influence of the Cost of Capital variable on Company Value. This research is a quantitative research with an explantory approach. The data used in this research is secondary data obtained through questionnaires from 250 employees in the fields of finance, HRD, HR and managers throughout Bank Danamon throughout Indonesia. The data obtained was analyzed with smart PLS 3.0 Keywords: Capital Cost, Good Coorporate Governance, Company Value